A Reconfigurable Run-Time System for Filter-Stream Applications - Fireman, Daniel; Teodoro, George; Cardoso, André; Ferreira, Renato (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
The development of high level abstractions for programming distributed systems is becoming a crucial effort in computer science. Several frameworks have been proposed, which expose simplified programming abstractions that are useful for a broad class of applications and can be implemented efficiently on distributed systems. One such system is Anthill, based on the filter-stream programming model, in which applications are decomposed into sets of independent filters that communicate via streams. Anthill achieves high performance by allowing filters to be transparently replicated across several compute nodes.In this paper we present a global state manager for Anthill, which exports a simple abstraction to manipulate state variables for application filters. The state is distributed transparently among the instances of that filter, and our manager is designed to allow data migration from one filter instance to another, enabling Anthill to dynamically reconfigure applications at execution time.To evaluate our system, we used two well known data mining algorithms: a priori and k-means. Our results show that the framework incurs low overhead, 1.8% on average, and that the resulting system can effectively make use of new resources as they are made available, with execution times 3.57% slower, on average, than the minimum expected time for the reconfiguration scenario.